Finite element analysis of elastomeric push-fit spigot and socket steel pipe joint - Abdul Aziz, Nuraini; Sahari, Barkawi; A. Khalid, Yousif; Idris, Azni (2001)
Spigot and socket push - fit joint is one of the methods, which can be used as pipe joining system. This technique was mostly used for small diameter pipe but has not been introduced for steel main pipe. With the co-operation from BOON & CHEAH STEEL PIPES SDN. BHD. company, a project has been developed to analyse the ability of the joint for 600mm steel pipes. Finite element method was used to analyse the ability of this joint. Two types of finite element software were used namely, LS-DYNA3D and LUSAS13. There were another two methods involved, theoretical and experimental methods, to support the finite element analysis of the joint. Elastomer, which was used in this study, used Mooney-Rivlin strain energy equation.!t has been identified that the permissible working pressure value for the joint occurred at the bottom surface of the elastomer. The value is higher than the water pressure in the pipe. From different cases studied by changing the thickness and width of the elastomer, the best pressure distribution developed was at t =3 mm and h = 0.5 l mm. For the pushing force analysis, it is identified that to fit the joint, the pushing force must exceed 10 kN. It is shown that the joint method can be used for large size steel pipe because the pressure value developed was higher than the internal water pressure. For the ease of joining, it has also been identified that the pushing force must be higher than the shear stress produced by the elastomer. Some recommendations have been proposed to get the most benefit of the analysis.